2021
DOI: 10.1039/d1na00251a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of unique intermetallic TiFe nanostructures originating from the morphology of oxide precursors

Abstract: TiFe nanostructures where prepared at temperatures as low as 600 °C with a Ti–Fe precursor and a CaH2 reducing agent in molten LiCl. For the first time an intermetallic compound with a unique layered morphology was found which could have originated from the FeTiO3 precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…These values are summarized in Table 1 . A larger crystallite size TiNi with a smaller BET surface area was obtained in this study compared with our previous results of TiFe (46.2–65.2 nm, 13.9–20.0 m 2 /g) [ 24 , 25 ]. Because nickel oxides are more easily reduced than iron oxide because of the more thermodynamic stability of FeO than NiO [ 37 ], the rate of crystal growth for TiNi crystal particles in the reduction/alloying processes at 650 °C could be accelerated to form the final larger particles.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…These values are summarized in Table 1 . A larger crystallite size TiNi with a smaller BET surface area was obtained in this study compared with our previous results of TiFe (46.2–65.2 nm, 13.9–20.0 m 2 /g) [ 24 , 25 ]. Because nickel oxides are more easily reduced than iron oxide because of the more thermodynamic stability of FeO than NiO [ 37 ], the rate of crystal growth for TiNi crystal particles in the reduction/alloying processes at 650 °C could be accelerated to form the final larger particles.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, it would be innovative to prepare titanium alloys directly from titanium oxides. We previously succeeded in preparing intermetallic compound TiFe powders from the oxide precursors, including TiO 2 [ 24 ] and FeTiO 3 [ 25 ] by directly reducing them and then alloying them simultaneously in highly reductive conditions of molten LiCl-CaH 2 at 600 °C. Under these conditions, hydride ions (H − ) or calcium metals that are produced from CaH 2 could as strong reducing agents to readily reduce the titanium oxide precursors at such a low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment followed ISO 14040 and ISO 14044 standards and the procedure applied in our previous works. 46,47 Goal and Scope Definition. The goal of this assessment was to quantify the life cycle GHG emissions of the HEA CrMnFeCoNi powder productions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A prospective LCA focused on greenhouse gas (GHG) emissions was performed to evaluate the environmental performance of the HEA CrMnFeCoNi powders. The assessment followed ISO 14040 and ISO 14044 standards and the procedure applied in our previous works. , …”
Section: Methodsmentioning
confidence: 99%
“…In 2021, we obtained nano-sized intermetallic TiFe with layered morphology via a nonelectrochemical method at 600 from molten LiCl-CaH 2 mixtures. [11] The layered structure was obtained by using FeTiO 3 as the precursor, whereas no layered structure was observed and instead spherical nanoparticles were observed when a FeÀ Ti oxide composed of Fe 9 TiO 15 , anatase TiO 2 , and rutile TiO 2 was used as the precursor. Thus, it was demonstrated that the layered intermetallic compound TiFe originated from FeTiO 3 precursor.…”
Section: Introductionmentioning
confidence: 99%